Use of “German-Games.Net” Site in an Online-Based German Vocabulary Learning at SMAN 3 Lamongan - Fidyah Wahyu Rahmadani (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The use of the site "german-games.net" aims to determine student activities in using the site "german-games.net" as a medium for learning German vocabulary online. This study also aims to determine students' responses to the use of the site "german-games.net". The subjects of this study were students of class XI Language at SMAN 3 Lamongan with a total of 25 students. The type of research used in this research is descriptive qualitative. Researchers obtained data from observations and interviews. Observations were made to find out the activity of using the "german-games.net" site in learning German vocabulary online. Researchers conducted interviews to determine student responses to the use of the "german-games.net" site. It provides a new learning experience for students, which is entertaining, encourages students to actively participate in online-based learning that results in positive outcomes.